Tracking of land vehicle motion with the use of distance measurements - Kraszewski, Tomasz; Czopik, Grzegorz (SPIE, 2019)
Today’s solutions of reconnaissance and electronic warfare systems require high accuracy in determining the location of the recognized object. It also involves the need to track the trajectory of the object's movement with particular attention to maneuvers and direction changes. The article presents a tracking simulation study of a land object carried out in MATLAB environment for generated various types of trajectories. For each case, the values of root mean square and relative errors are determined. These errors, as well as the evaluation of graphical imaging, allow to assess the usefulness of implemented tracking algorithms using nonlinear Kalman’s filtration. In the next stage, measurements were taken in real terms using a system built from four stationary ultra-wideband (UWB) modules and one mobile built-in land vehicle. The measurement data contained both the raw distance data and the locations obtained from the system tracking application. At this stage, preliminary verification of the designed tracking algorithms was carried out using raw distance data between the modules and the object to create own tracking application. The results of the above operations for different trajectories are presented in the form of appropriate graphical imagery. They confirm the possibility to track the trajectory of a land object using distance measurement from ultra-wideband modules based on the own implemented algorithms. The determination of location is made with high accuracy while improving parameters in relation to factory algorithms at the time of maneuver.